GAMBARAN TINGKAT PENGETAHUAN TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT DENGAN TERJADINYA KARIES GIGI PADA SISWA KELAS VI DI SDN SINDANGBARANG 2 (Jurnal Terapi Gigi dan Mulut, 2023)
Knowledge is the result of knowing someone about an object or something through the senses they have. Knowledge is very influential in shaping one's actions, one of which is in maintaining dental and oral health. One of the most common dental and oral health problems experienced by the community is dental caries. Dental caries is damage to the hard tissues of the teeth starting from the tooth surface (pits, fissures and interproximal areas) to extending to the dentin and pulp and can occur on one or more tooth surfaces. The purpose of this study was to describe the level of knowledge about the maintenance of dental and oral health with the occurrence of dental caries in class VI students at SDN Sindangbarang 2. This research is a descriptive study, the sampling technique used was total sampling technique. The results of research conducted on 38 students showed that the level of knowledge about dental and oral health maintenance which was categorized as good was 17 people (44.7%), medium category was 12 people (31.6%), and less category was 9 people ( 23.7%) and the average dental caries index in students was 1.26. The conclusion of this study is that the majority of students have a good level of knowledge about dental and oral health maintenance with 17 people (44.7%) and the average dental caries index in the low category with a value of 1.26.